The Significance of Women's Imamate in Shalat: Analysis of Ma’na Cum Maghza on the Hadith of Ummi Waraqah) - Masiyan M. Syam; Ahmad Mustaniruddin; Faisal Haitomi; Taufiq Al-Faruq (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to find the significance (main message) or maghza of the hadith text regarding the position of Imamatein prayer. This study is a qualitative research method with ama'na cum maghza of hermeneutical approach as an analytical tool. The debate over the position of women as Imamate over men is a hot issue that continues to this day. The majority of debates among scholars so far have only focused on the authenticity of indicating whether the hadith is authentic, hasan, or daif, without looking at the important issues contained in the context of the hadith. This study concludes that the hadith about Ummu Waraqah being an Imamate for men is an affirmation by the Prophet Muhammad SAW regarding gender equality. It has implications for the legality of women becoming Imamate over men based on a fluent understanding of prayer procedures and qiraat Al-Qur'an, the legality of women's struggles in defending religion, and the legality of women's leadership both in the domestic and public spheres